PEMBUATAN SIMPING HERBAL DARI DAUN BELUNTAS (Plucea Indica (L) Less) UNTUK PERAWATAN KESEHATAN - Jayadinata, Egi Prastika; Andriani, Susi; Ratnasari, Dewi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Objective: This research aims to provide healthy snacks so that preparations can be used by the community for health care. Method: In this research he did approach a qualitative research method of action developed from previous research on efficacy of leaf Beluntas (Plucea Indica (L) Less). In this study researchers make healthy snacks from the leaves of Beluntas (Plucea Indica (L) Less) in the form of the scallop through the process of with infusa solvent water was mixed on basic material i.e. simping tapioca flour and flour wheat flour. Simping is made by mixing 1 liter water infusa leaf Beluntas (Plucea Indica (L) Less) with tapioca flour 1.25 kg, 0.25 kg of wheat flour, coconut milk 240 ml, and 37 g of salt. Result: The resultof theorganoleptis preparations testing done for 21 days with the results show that there is no negative changes that occurred from the shape, color, smell, taste, or whether or not there is mold growth. Conclusion: In this study the researchers managed to make healthy snacks in the shape of a healthy snack can last for 3 weeks.